#SHAPEsoWhite. (3rd May 2020) - Blackshear, Tara B.
ABSTRACT: Purpose: The purpose of this paper is to investigate the racial/ ethnic diversity of SHAPE America's teacher of the year program using Critical Race Theory. As such, the goal was to identify and map potential racial biases within the institutional structures of SHAPE America's teacher of the year program. Research design and methods: This paper used an exploratory research design using online Physical Education Teacher of the Year online profiles, social media requests, emails, and demographic questionnaires. Data collected from the design included the breakdown of nominees and recipients between 2008–2018. Data were analyzed in two different ways. First, the data were inductively analyzed using descriptive statistics, including frequency and percentages of SHAPE America Teachers of the Year. Second, a critical race lens was used to interpret the descriptive statistics in relation to the selection process and larger social issues. Results: The overwhelming number of SHAPE teachers of the year were white women with the second demographic being white men. For this reason, there seems to be a lasting effect of racism on SHAPE America's institutional structure, as well as dominant groups, in this case white women, benefitting from these racist practices. Conclusions: Teachers of Color are virtually non-existent in SHAPE's Physical Education Teacher of the Year program. I argue this is problematic for two overarching reasons. From a critical race perspective, SHAPE America's teacher of the year program is reproducing racial inequities for PE teachers. Second, such racial inequities are tied to larger societal issues. Considering that SHAPE America has recently promoted social justice issues, I finish the paper by making suggestions for the TOY selection process that can promote racial inclusiveness.